2001
DOI: 10.1093/emboj/20.4.864
|View full text |Cite
|
Sign up to set email alerts
|

The adenovirus E4-ORF4 splicing enhancer protein interacts with a subset of phosphorylated SR proteins

Abstract: SR proteins puri®ed from uninfected HeLa cells inhibit adenovirus IIIa pre-mRNA splicing by binding to the intronic IIIa repressor element (3RE). In contrast, SR proteins puri®ed from late adenovirusinfected cells are functionally inactivated as splicing repressor proteins by a virus-induced dephosphorylation. We have shown that the adenovirus E4-ORF4 protein, which binds the cellular protein phosphatase 2A (PP2A) and activates IIIa splicing in vitro and in vivo, induces SR protein dephosphorylation. Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 46 publications
4
66
0
Order By: Relevance
“…In support of such a conclusion we have previously shown that the regulated activation of IIIa splicing does not require cis competition in vitro (22). Also, our previous results have suggested that IIIa splicing is actively repressed in early infected cells by SR proteins binding to the 3RE (10), a repression that is relieved at the late phase of infection by a virus-induced dephosphorylation of SR proteins (23,24). Furthermore, the 3VDE, which binds U2AF inefficiently (11,12), adds to the low activity of IIIa splicing at early times of infection.…”
Section: Discussionmentioning
confidence: 54%
“…In support of such a conclusion we have previously shown that the regulated activation of IIIa splicing does not require cis competition in vitro (22). Also, our previous results have suggested that IIIa splicing is actively repressed in early infected cells by SR proteins binding to the 3RE (10), a repression that is relieved at the late phase of infection by a virus-induced dephosphorylation of SR proteins (23,24). Furthermore, the 3VDE, which binds U2AF inefficiently (11,12), adds to the low activity of IIIa splicing at early times of infection.…”
Section: Discussionmentioning
confidence: 54%
“…Its contribution involves down-regulation of expression of cellular and early viral genes (1)(2)(3)(4)(5), induction of alternative splicing of viral mRNAs (6,7), and regulation of protein translation through an interaction with the mTOR pathway (8). When expressed outside the context of viral infection, E4orf4 induces nonclassical apoptosis that is caspase-independent in many cell lines and which is preceded by G 2 /M arrest (9 -11).…”
mentioning
confidence: 99%
“…Furthermore, at least part of the E4orf4 signaling network is highly conserved in evolution from yeast to mammalian cells (10,(13)(14)(15), underscoring its importance to cell regulation. Studies of the mechanisms underlying E4orf4 action have revealed several E4orf4 partners, including the B55/B␣ (16) and B56 (17) subunits of protein phosphatase 2A (PP2A), the ATP-utilizing chromatin assembly and modifying factor (ACF) (18), Src family kinases (19,20), the anaphase-promoting complex/cyclosome in the budding yeast (10), a subset of splicing serine/arginine-rich proteins (6), and Ynd1/Golgi uridine diphosphatase (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by dephosphorylating inhibitory SR proteins, E4orf4 activates the process of mRNA splicing. 90,91 It is not currently known whether these molecules are the direct targets of the E4orf4-PP2A complex and/or whether these molecules play a role in E4orf4 mediated cell death.…”
Section: E4orf4 -Another Tumor-selective Killermentioning
confidence: 99%